Estudio de factibilidad para la implementación de un centro de acopio de cacao (Theobroma Cacao) para la Cooperativa Agrícola “Recreo del Congo” del cantón Buena Fe año 2013. - Rivera Figueroa, Glenda Katherine (2015)
In canton Buena Fe province of Los Rios for being a mainly productive and commercial cultivation of cocoa as it has developed accelerating agriculture involves strengthening all value chains so that small producers compete to achieve the cooperative agricultural " Congo Recess " for what they have been marginalized for years , that is why we have seen the need to implement these types of projects for social and economic benefits through social institutions , the municipality of good faith or minded state modern agricultural improving the quality of life. To meet the objectives of the investigation proceeded to conduct field visits , where it was found ground facilities which implement the collection center , and with the help of a camera , tape measure could register the building air same , and then make a design center projected . The storage center will be built on a plot of 828m2; its infrastructure will consist of: a warehouse, a trail, a dryer, a fermenting shed, canopies and guard booth with a construction area of approximately 396.75 square meters which $ 72,820 would be spent. The collection center facilities have a capacity to process 600 pounds of cocoa ready for commercialization monthly, i.e. it can process 7200 quintals annually. Restriction remains as processing capacity between service delivery and benefit processing and cocoa….